Subspecies and Distribution. L.o.othusMerriam,1900—WAlaska(USA). L.o.poadromusMerriam,1900—AlaskaPeninsula(USA). L. o. tschuktschorum Nordqvist, 1883 — Chukchi Peninsula, NE Siberia (Russia). in Leporidae - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
Subspecies and Distribution. L.o.othusMerriam,1900—WAlaska(USA). L.o.poadromusMerriam,1900—AlaskaPeninsula(USA). L. o. tschuktschorum Nordqvist, 1883 — Chukchi Peninsula, NE Siberia (Russia). Published as part of Don E. Wilson, Thomas E. Lacher, Jr & Russell A. Mittermeier, 2016, Leporidae, pp. 107-148 in Handbook of the Mammals of the World – Volume 6 Lagomorphs and Rodents I, Barcelona :Lynx Edicions on page 145, DOI: 10.5281/zenodo.6625539